Circular - Morgan, Betty
1939-10 038-0073-001 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: DR. BETTY MORGAN. 30, ECCLESTON STREET, [4, GREAT SMITH STREET,] LONDON, S.W.1. TELEPHONE: [ABBEY 2565] SLOANE 9866 Dear Friends: In existing war conditions, we trust that the following notes, drawn up at the request of several Basque Children's Homes and Basque Children's Committees, may be of assistance to you. 1. The Basque Children's Committee and the National Joint Committee for Spanish Relief will make every effort to return to Spain all children who are claimed by their parents or whose parents in Spain are in a position to receive them. It is likely that the outbreak of hostilities will lead to a number of fresh claims for repatriation, and we are making approaches to the Foreign Office and other competent authorities to find out what transport arrangements can be made between England and Spain under existing conditions. 2. It should be borne in mind, however, that the majority of the children still in this country have parents who are refugees in France, and who have repeatedly asked us not to let their children return to Franco's Spain. To return these children would not merely be a breach of our promise to their parents, it might also lead to life-long separation between parents and children. In this respect our duty is clear: we have here a commitment which we cannot honorably repudiate. 3. We undertook originally that the Basque Children should not be a charge on public funds, and we cannot count on any assistance from the Government. We are therefore more than ever dependent upon voluntary contributions. 4. As funds at the disposal of the National Joint Committee and the Basque Children's Committee are very low, and are already largely earmarked for the support of adult refugees, it is of vital importance that we should redouble our efforts to make the Basque children financially secure. Otherwise, we may have no alternative but to return them to Spain, against their parent's wishes, and their own. 5. We therefore suggest that homes should make strenuous and immediate efforts to place their children in private families. Local Branches of the National Joint Committee have been asked to co-operate in this task, and we suggest that you should get in touch with the organisation nearest to you. Already, a number of our children from the Midlands have been placed in private homes through the help of N.J.C. local and regional Committees . The children have made many friends during the two and a half years of their exile in England, and we feel sure that these will now rally to their assistance. 6. In this national emergency, there is likely to be plenty of work of national utility that the older boys and girls at our Basque homes can perform. Already all the older children in one of our homes near London have been absorbed in this way. Their earnings help to make the home self-supporting, the children themselves are happy to be working, and the result is in every way satisfactory. We therefore urge you to try and 292/946/38/73(I)